The Williams-Hunt collection aerial photographs and cultural landscapes in Malaysia and Southeast Asia - Elizabeth Moore (Universiti Kebangsaan Malaysia, 2009)
Cultural and academic links between SOAS and the Institute of the Malay World and Civilization (ATMA), Universiti Kebangsaan Malaysia (UKM) include academic and cultural exchange. The Williams-Hunt Collection (SOAS) of aerial photographs adds an archival dimension stemming from the life and work of Peter Williams-Hunt (1919-1953). Williams-Hunt is best known for his role as Advisor to the Aborigines in Malaysia shortly after World War II. During this period, he wrote several seminal articles on the Orang Asli. He was also a trained aerial photographic interpreter and collected more than 5000 aerial photographs of Malaysia, Singapore, Myanmar, Thailand, Cambodia and miscellaneous areas of Vietnam during his postings to Southeast Asia during the war. The author had new copies made of the old photographs and compiled them into a database as part of her doctoral work in the 1980s. At present, thanks to collaboration with Surat Lertlum in Thailand, many parts of the aerial archive are now available online. The article summarizes aspects of the Williams- Hunt Collection and discusses the unique contribution made by Williams-Hunt to archaeology, anthropology and museum collections. His work on ancient settlements pioneered the analysis of the archaeological landscape and his anthropological study was the first to document the changing pattern of the landscape of the many different groups cultivating the forested regions of peninsular Malaysia